Memory CD4+ T cells are generated in the human fetal intestine - Li, Na; van Unen, Vincent; Abdelaal, Tamim; Guo, Nannan; Kasatskaya, Sofya A; Ladell, Kristin; McLaren, James E; Egorov, Evgeny S; Izraelson, Mark; Chuva de Sousa Lopes, Susana M; Höllt, Thomas; Britanova, Olga V; et al. (Nature immunology, 2019)
The fetus is thought to be protected from exposure to foreign antigens, yet CD45RO+ T cells reside in the fetal intestine. Here we combined functional assays with mass cytometry, single-cell RNA sequencing and high-throughput T cell antigen receptor (TCR) sequencing to characterize the CD4+ T cell compartment in the human fetal intestine. We identified 22 CD4+ T cell clusters, including naive-like, regulatory-like and memory-like subpopulations, which were confirmed and further characterized at the transcriptional level. Memory-like CD4+ T cells had high expression of Ki-67, indicative of cell division, and CD5, a surrogate marker of TCR avidity, and produced the cytokines IFN-γ and IL-2. Pathway analysis revealed a differentiation trajectory associated with cellular activation and proinflammatory effector functions, and TCR repertoire analysis indicated clonal expansions, distinct repertoire characteristics and interconnections between subpopulations of memory-like CD4+ T cells. Imaging mass cytometry indicated that memory-like CD4+ T cells colocalized with antigen-presenting cells. Collectively, these results provide evidence for the generation of memory-like CD4+ T cells in the human fetal intestine that is consistent with exposure to foreign antigens.
Keywords: Gene Expression Regulation, Developmental; High-Throughput Nucleotide Sequencing; Antigen-Presenting Cells; vývojová regulace genové exprese; Ki-67 Antigen; Humans; plod; Cells, Cultured; Immunophenotyping; CD4-pozitivní T-lymfocyty; kultivované buňky; průtoková cytometrie; lidé; imunologická paměť; Immunologic Memory; CD4-Positive T-Lymphocytes; Fetus; antigen prezentující buňky; Intestines; vysoce účinné nukleotidové sekvenování; Gene Expression Profiling; stanovení celkové genové exprese; antigeny CD5; imunofenotypizace; střeva; CD5 Antigens; antigen Ki-67; Flow Cytometry